Políticas de contenção de desmatamento, produção e mercado de terras na Amazônia: um ensaio sobre a economia local do sudeste paraense usando contas sociais alfa (CSa) - Costa, Francisco de Assis (Estudos Econômicos (São Paulo), 2011)
The current discussion on avoiding carbon emission associated to agricultural use of land needs a more systemic approach, whether in regard to the economic flows properly and their interactions, whether in terms of the institutional environment that ensures them. Given that avoiding deforestation schemes implicate resources input-output throughout local economies and broader economic context, it seems fundamental to discuss what are the final impacts of those flows. The basic questions are: a) how such policies, starting from the rural sectors, will affect final demand, the value of the production and the variables of value added all over the economy and b) how variations in the economy affect the forms of use of natural resources and, therefore, deforestation itself. Related to institutions, the article puts special emphasis on defining the market for land, because it is the core of vital issues. The article uses an ascending model to generate input-output matrices for local economies based on primary products, where works a market for land, incorporates an algorithm of carbon balance, finds the multipliers of the economy of Southeastern Pará and simulates four situations of policies on avoiding deforestation. The main conclusion is that policies for avoiding deforestation will probably have a hard time if not part of macro development policy on local level.